Eco and CFA Franc: Continuation or Rupture of Colonial Legacies in Postcolonial Monetary Sovereignty? - Lassana Kanté (Jurnal Perpajakan dan Keuangan Publik, 2025)
CFA has been created in 1945 by colonial France. CFA has stood for Colonies Françaises d’Afrique with fourteen West African countries. The West African space is divided in two zones: the West African Economic and Monetary Community called WAEMU (UEMOA in French), and the Central African Economic and Monetary Community also known as CAEMC or CEMAC in English. CFA has been guaranteed by the French Treasury and pegged by the euro. It was partially governed by colonial France. In Contrast, Eco refers to a single currency that the Economic Community of West African States (ECOWAS) proposed for the economic integration and monetary independence in West Africa. In opposition to CFA, the Eco has been designed as decoupled from the institutions of France. The latter reflects pan-African economic identity and ideology. The objective of the present paper is to analyze the representation of neocolonialism in reference to the two economic currencies. In other words, we aim to study the decolonial image of West African monetary currency in reference the transition from CFA to Eco.